Operating properties of the coating, depending on the composition during plasma-chemical modification. (October 2019) - Bondarenko, D O; Strokova, V V
Abstract: Compositions of protective and decorative coatings on the basis of a mixture of high alumina refractory, liquid glass and dyeing salts of metals are developed. The color of the coatings depends on the type of dyeing salt and the concentration of the aqueous solution. Data on the effect of the composition on the operational properties of vitreous coatings obtained by the method of plasma-chemical modification are presented. The increased content of aluminium and silicon oxides provides an improvement in a number of characteristics such as microhardness, heat resistance, water resistance and acid resistance, which are essential in the formation of protective and decorative coating. It is established that at the rate of plasma jet passage up to 15 mm/s a protective-decorative coating with uniform texture is formed, at the rate of plasma jet passage 20 mm/s and more the coating represents a hilly surface with separate and congested deformed drops of frozen melt.